Penetration, distribution, and elimination of remofuscin/soraprazan in Stargardt mouse eyes following a single intravitreal injection using pharmacokinetics and transmission electron microscopic autoradiography: Implication for the local treatment of Stargardt's disease and dry age‐related macular degeneration. Issue 6 (8th November 2020) - Julien‐Schraermeyer, Sylvie; Illing, Barbara; Tschulakow, Alexander; Taubitz, Tatjana; Guezguez, Jamil; Burnet, Michael; Schraermeyer, Ulrich
Abstract: Age‐related macular degeneration (AMD) is the leading cause of blindness in older people in the developed world while Stargardt's disease (SD) is a juvenile macular degeneration and an orphan disease. Both diseases are untreatable and are marked by accumulation of lipofuscin advancing to progressive deterioration of the retinal pigment epithelium (RPE) and retina and subsequent vision loss till blindness. We discovered that a small molecule belonging to the tetrahydropyridoether class of compounds, soraprazan renamed remofuscin, is able to remove existing lipofuscin from the RPE. This study investigated the drug penetration, distribution, and elimination into the eyes of a mouse model for increased lipofuscinogenesis, following a single intravitreal injection. We measured the time course of concentrations of remofuscin in different eye tissues using high‐performance liquid chromatography combined with mass spectroscopy (HPLC‐MS). We also visualized the penetration and distribution of 3 H‐remofuscin in eye sections up to 20 weeks post‐injection using transmission electron microscopic (TEM) autoradiography. The distribution of silver grains revealed that remofuscin accumulated specifically in the RPE by binding to the RPE pigments (melanin, lipofuscin and melanolipofuscin) and that it was still detected after 20 weeks. Importantly, the melanosomes in choroidal melanocytes only rarely bind remofuscin emphasizing its potential to serve as an active ingredient in the RPE for the treatment of SD and dry AMD. In addition, our study highlights the importance of electron microscopic autoradiography as it is the only method able to show drug binding with a high intracellular resolution. Abstract : TEM autoradiography shows: a depot effect of remofuscin that could be relevant for a local application of the drug. The RPE specificity of the drug. Only TEM autoradiography allows the investigation of drug binding with high intracellular resolution.